Embedding hospital-based medication review: The conflictual and developmental potential of a practice. Issue 3 (18th April 2019) - Reichenpfader, Ursula; Wickström, Anette; Abrandt Dahlgren, Madeleine; Carlfjord, Siw
Abstract : Purpose: The purpose of this paper is to explore the embedding of hospital-based medication review attending to the conflictual and developmental nature of practice. Specifically, this paper examines manifestations of contradictions and how they play out in professional practices and local embedding processes. Design/methodology/approach: Using ethnographic methods, this paper employs the activity-theoretic notion of contradictions for analyzing the embedding of medication review. Data from participant observation (in total 290 h over 48 different workdays) and 31 semi-structured interviews with different healthcare professionals in two Swedish hospital-based settings (emergency department, department of surgery) are utilized. Findings: The conflictual and developmental potential related to three interrelated characteristics (contested, fragmented and distributed) of the activity object is shown. The contested nature is illustrated showing different conceptualizations, interests and positions both within and across different professional groups. The fragmented character of medication review is shown by tensions related to the appraisal of the utility of the newly introduced practice. Finally, the distributed character is exemplified through tensions between individual and collective responsibility when engaging in multi-site work. Overall, the need for ongoing "repair" work is demonstrated. Originality/value: By using a practice-theoretical approach and ethnographic methods, this paper presents a novel perspective for studying local embedding processes. Following the day-to-day work of frontline clinicians captures the ongoing processes of embedding medication review and highlights the opportunities to learn from contradictions inherent in routine work practices.